c.3 - Myrdal, Gunnar (London, 1960)
This little book is concerned with the trend towards economic planning in the rich and progressive Western countries, and with the international implications of this trend. In Part I an attempt is made to throw some light on the interplay of social forces which have resulted in this trend, and on the type of national community which is emerging. Part II is devoted to the effects of national economic planning in these countries on their economic relations with each other and with the rest of the world, in particular with the under-developed countries in the non Soviet world.
Keywords: Economic policy